La "Vita S. Petri ep. Oxomensis" (BHL 6760-61): edición y estudio del oficio completo en honor del obispo Pedro de Osma - Martín-Iglesias, José Carlos 1968- (Analecta Bollandiana: Revue critique d'hagiographie, 2014)
The Vita s. Petri ep. Oxomensis (BHL 6760-6761) is a prose account of bishop Pedro de Osma († 1109). It was written probably in the second half of the 12th century by a canon of the church of Santa María de Osma, who was perhaps of French origin. The article contains the first complete edition of the liturgical office in honour of the bishop on the basis of the sole manuscript with the entire corpus made up not only of the Vita s. Petri ep. Oxomensis but also of hymns, prayers, antiphons and responses, viz. fifteenth-century codex 2B of the Cathedral Library, Burgo de Osma.